2014
DOI: 10.4238/2014.september.29.12
|View full text |Cite
|
Sign up to set email alerts
|

Study of human acellular amniotic membrane loading bone marrow mesenchymal stem cells in repair of articular cartilage defect in rabbits

Abstract: ABSTRACT. The aim of this study was to investigate the repair effect of human acellular amniotic membrane (HAAM) loading bone marrow mesenchymal stem cells (BMSCs) on articular cartilage defect in rabbits. Rabbit BMSCs were isolated and cultured, and they were then inoculated on HAAM to prepare the complex of HAAM and BMSCs. Twenty-four rabbits were randomly divided into groups A and B, with 12 animals in each group. The left and right sides were used as the experimental and control sides, respectively. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Thus, AHAM provide a favourable environment for the in‐migration, proliferation, and differentiation of chondrocytes and epithelial cells. Our findings are consistent with previous reports showing that AHAM engraftment improves the repair of articular cartilage defects in rabbits through the enhanced cultivation of bone marrow mesenchymal stem cells (Liu et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Thus, AHAM provide a favourable environment for the in‐migration, proliferation, and differentiation of chondrocytes and epithelial cells. Our findings are consistent with previous reports showing that AHAM engraftment improves the repair of articular cartilage defects in rabbits through the enhanced cultivation of bone marrow mesenchymal stem cells (Liu et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Of note, the combination of amniotic membrane treatment and MSCs has shown better therapeutic effects than amniotic membrane treatment alone in patients with ocular chemical burns, skin defects, and articular cartilage defects. 47,48 Thus for some severe ocular disorders, the combination of amniotic membrane treatment and MSCs or MSC-CMT might be a promising therapy.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the HAAM scaffold has been used in many fields, especially in repairing skin defects [45]. In recent years, an increasing number of studies have found that the HAAM scaffold had a positive effect on orthopedic diseases, such as promoting bone regeneration and repairing articular cartilage defects [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other methods, this method offered many advantages, such as quicker results, simpler process, and lower cost. Although this method to prepare the HAAM scaffold has been used in other studies [47,50], we reduced the duration taken for enzymatic digestion, improving the integrity of the extracellular matrix and reducing time and cost. HE staining was performed on fresh HAM and HAAM scaffolds in order to confirm thorough decellularization of HAM.…”
Section: Discussionmentioning
confidence: 99%